Product development projects and ways to improve and manage them - case company X - Mars, Tiia (My University, 2021)
This thesis work focuses on project management in product development projects. Meaning and purpose of projects and project management is looked at, as well as different project management methodologies. The research section of the work presents a qualitative research done on the subject of improving project work in product development for a case company that wishes to stay anonymous. The study results are analyzed and from them a conclusion and recommendation delivered to the company. The strategic starting point of this work is the case company’s wish to gain more efficiency and tools to be used in product development projects. The theoretical framework is formed so that it gives a good understanding on the background of the research topic.
Keywords: projects; project management; project work; product development; agile methods; fi=Tuotantotalous (kauppatieteet)|en=Industrial Management|; Master's Programme in Industrial Management